The two domains of Mycobacterium tuberculosis NusG protein are dynamically independent. Issue 2 (1st February 2016) - Strauß, Martin; Schweimer, Kristian; Burmann, Björn M.; Richter, Anne; Güttler, Stephanie; Wöhrl, Birgitta M.; Rösch, Paul
Abstract : Transcription elongation factor NusG from Escherichia coli couples transcription and translation. It is the only conserved transcription factor in all three kingdoms of life, playing a variety of roles in gene expression. E. coli NusG consists of two non-interacting domains. While the N-terminal domain interacts with RNA polymerase, the C-terminal domain contacts NusE (S10), or the Rho transcription termination factor. The two corresponding domains of Thermotoga maritima NusG are mutually interacting. Therefore, NusG here forms an autoinhibited state, where the binding sites to RNAP, NusE, and the Rho factor are masked. Recent functional studies showed differences between NusG from E. coli and Mycobacterium tuberculosis . In contrast to E. coli NusG, M. tuberculosis NusG is able to stimulate intrinsic termination, but is not able to bind the Rho factor. To analyze whether this has structural reasons, we determined the solution structure of the carboxyterminal domain of M. tuberculosis NusG by nuclear magnetic resonance spectroscopy. Furthermore, we modeled the wild-type full-length protein, and present evidence that the two domains of this protein do not interact in solution by NMR dynamics measurements.